Complicating Patriarchy: Gender Beliefs of Muslim Facebook Users in the Middle East, North Africa, and South Asia. Issue 1 (February 2023) - Charles, Maria; Friedland, Roger; Afary, Janet; Yang, Rujun
Western stereotypes often characterize gender relations in Muslim-majority societies as uniformly traditional and patriarchal. Underlying this imagery is a unidimensional understanding of gender ideology as moving along a single traditional-to-egalitarian continuum. In this study, we interrogate these assumptions by exploring variability across and within Middle Eastern, North African, and South Asian (MENASA) societies in beliefs related to two regionally salient gender principles: women's chastity and marital patriarchy. Data from a new online survey of Muslim Facebook users show substantial heterogeneity across and within six MENASA societies in support for these principles. These data also reveal a multidimensional structure, in that societies show different configurations of chastity and marital patriarchy beliefs, and each of these gender principles is influenced by respondents' religious beliefs and gender status in different ways. Although religious absolutism predicts agreement with both gender principles, piety is associated with support for chastity but not for marital patriarchy. Results also show a clear gender divide in attitudes toward hierarchy in marriage but not with respect to chastity. Findings complicate broad-brush depictions of patriarchy in the region and corroborate previous research on the multidimensionality of gender beliefs and the multifaceted attitudinal influences of gender and religious beliefs.